Benefit Incidence Analysis for Maternal and Child Health Services in Kenya - Geofrey Mwalo; Urbanus Mutuku Kioko (European Scientific Journal, ESJ, 2026)
Background: Financing maternal and child healthcare services is a common practice in most countries and the method of administration lies fundamentally on the distributional issues, that is, the health sector specific equity objectives such as equal treatment for equal need. The subsidies therefore should be target efficient such that only the poor receive them. This study sought to address the questions in public policy strategies, such as, how well public resources are spent on healthcare, to assess if the benefits ultimately reach the poorest segment of the population and whether the general public spending on healthcare services is pro-poor. The overall aim of the study was to establish the benefit incidence of the maternal and child health services in Kenya.Methods: The benefit incidence analysis approach employed in this study assessed the accrued benefits of maternal and child health care subsidies across various socioeconomic segments in Kenya. The research utilized the Kenya demographic health survey data (2013/14) and the national health account data (2013/14) to establish the per capita subsidy of maternal and child healthcare utilization across population in relation to their wealth index.Results: The study results indicated income related inequality in maternal and child health care utilization in Kenya and the pattern differed across wealth quantiles in different geographical areas. The distribution of the total subsidy was pro-poor, however, when the results were expressed as a proportion of household total expenditure, the results indicated that the rich received a subsidy that was a larger proportion of their expenditure compared to that received by the poorest populationConclusion: Significant pro-poor inequality was observed in urban and private facilities indicating that more effective targeting of maternal and child care is necessary. Eliminating financial and non-financial barriers for the poor and higher need group in rural areas would make a key contribution in reducing pro-rich inequality in outpatient maternal and childcare utilization.